2013
DOI: 10.5009/gnl.2013.7.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Miniprobe Endoscopic Ultrasonography Has Limitations in Determining the T Stage in Early Colorectal Cancer

Abstract: Background/AimsMini-probe endoscopic ultrasonography (mEUS) is a useful diagnostic tool for accurate assessment of tumor invasion. The aim of this study was to estimate the accuracy of mEUS in patients with early colorectal cancer (ECC).MethodsNinety lesions of ECC underwent mEUS for pre-treatment staging. We divided the lesions into either the mucosal group or the submucosal group according to the mEUS findings. The histological results of the specimens were compared with the mEUS findings.ResultsThe overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…2) for T1 staging, which is in agreement with previous reports (21,22). With regard to T2 staging, 3D was superior to mp-EUS, which tended to overstage tumors (12,16,17,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2) for T1 staging, which is in agreement with previous reports (21,22). With regard to T2 staging, 3D was superior to mp-EUS, which tended to overstage tumors (12,16,17,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 81%
“…Miniprobe EUS (mp-EUS) may easily overcome these obstacles due to its reduced diameter and flexibility (8,9). mp-EUS may be the most adequate ultrasonographic tool for the differential diagnosis of tumors limited to the mucosa (T1m) or with involvement of the submucosa (T1sm) as it uses high frequencies and thus resolves the limitations of C-EUS (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…They found that miniprobe endoscopic sonography had high accuracy in determining the depth of colorectal lesions and was useful before endoscopic resection. However, miniprobe endoscopic sonography has limitations in determining the tumor stage in early colorectal cancer, and the accuracy decreased when the tumor size was greater than 2 cm or the tumor had invaded the submucosal layer (Table ) …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the usefulness of endoscopic ultrasonography (EUS) for estimating the invasion depth [ 15 18 ]. However, the echoendoscope can be applied only to distal colorectal lesions, and the use of a miniprobe may be limited due to the probe's insufficient penetration depth for the estimation of large protruded tumors [ 19 ].…”
Section: Discussionmentioning
confidence: 99%